High resolution real time ultrasonography of the sural nerve after percutaneous repair of the Achilles tendon. Issue 4 (August 2018) - Zappia, Marcello; Berritto, Daniela; Oliva, Francesco; Maffulli, Nicola
Highlights: High resolution real time ultrasonography was evaluated for assessing the sural nerve injury during the percutaneous Achilles tendon repair. The sural nerve can be easily visualized by high-frequency ultrasonography probes. The sural nerve was found to be entrapped in 2 of 7 operated cadaveric limbs. Pre or intraoperative high resolution real time ultrasonography could minimize the risks of percutaneous Achilles tendon repair. Abstract: Background: Percutaneous Achilles tendon repair has been developed to minimise soft tissue complications following treatment of tendon ruptures. However, there are concerns because of the risk of sural nerve injury. Few studies have investigated the relationship between the Achilles tendon, the sural nerve and its several anatomical course variants. Methods: We studied 7 cadaveric limbs (7 Achilles tendons) in which a percutaneous repair of the Achilles tendon was performed. On each tendon, high resolution real time ultrasonography examination was performed by an experienced musculoskeletal radiologist before and after the procedure, with the surgeons blind to the results of the scan both before and after surgery. Results: In two instances, high resolution real time ultrasonography examination revealed nerve entrapment at the level of most proximal lateral suture. Conclusions: Since the sural nerve can be easily visualised using high-frequency high resolution real time ultrasonography, intraoperative ultrasound can be of assistance during percutaneous repair of Achilles tendon rupture. Clinical relevance: The sural nerve can be readily visualised by high-frequency high resolution real time ultrasonography probes. It could be beneficial to use high resolution real time ultrasonography intraoperatively or perioperatively to minimise the risks of sural nerve injury when undertaking percutaneous repair of Achilles tendon tears.